Paideia: commentaries on the New Testament : First and Second Thessalonians - Brookins, Timothy A. (Grand Rapids, MI. Baker Academic, 2021)
Though often neglected among readers of Paul's letters, his two surviving letters to the church in Thessalonica are highly valuable sources for reconstructing the theology of Paul and the history of the earliest Christian churches. First and Second Thessalonians also stand out for their intensely personal nature and provide a rare glimpse into Paul's methods of pastoral care. This practical commentary interacts with the best scholarship on the Thessalonian letters while offering fresh new insights.
Includes bibliographical references and index.
Keywords: Bible. -- Commentaries; Commentaries